2023
DOI: 10.1001/jamanetworkopen.2022.53590
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of COVID-19 as the Underlying Cause of Death Among Children and Young People Aged 0 to 19 Years in the US

Abstract: ImportanceCOVID-19 was the underlying cause of death for more than 940 000 individuals in the US, including at least 1289 children and young people (CYP) aged 0 to 19 years, with at least 821 CYP deaths occurring in the 1-year period from August 1, 2021, to July 31, 2022. Because deaths among US CYP are rare, the mortality burden of COVID-19 in CYP is best understood in the context of all other causes of CYP death.ObjectiveTo determine whether COVID-19 is a leading (top 10) cause of death in CYP in the US.Desi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
58
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(64 citation statements)
references
References 18 publications
4
58
1
1
Order By: Relevance
“…Findings from the period when wild-type SARS-CoV-2 virus was predominant (March-December 2020) showed that late preterm and term newborns (≥34 gestational weeks) with COVID-19 had an increased risk of neonatal intensive care unit (ICU) admission and early preterm newborns (<34 gestational weeks) with COVID-19 had an increased risk of invasive ventilation support [4]. Further, COVID-19 was a leading cause of death for infants <1 year during 2021-2022 [5].…”
Section: Introductionmentioning
confidence: 99%
“…Findings from the period when wild-type SARS-CoV-2 virus was predominant (March-December 2020) showed that late preterm and term newborns (≥34 gestational weeks) with COVID-19 had an increased risk of neonatal intensive care unit (ICU) admission and early preterm newborns (<34 gestational weeks) with COVID-19 had an increased risk of invasive ventilation support [4]. Further, COVID-19 was a leading cause of death for infants <1 year during 2021-2022 [5].…”
Section: Introductionmentioning
confidence: 99%
“…While most children experience mild symptoms with acute SARS-CoV-2 infection, severe complications can ensue, even in the youngest children, and myocarditis, cardiomyopathy, renal failure, as well as coagulation and hemorrhagic disorders occur at increased rates with COVID-19 2 . Concerningly, COVID-19 deaths in children far exceed deaths from influenza 3 and COVID-19 has now become one of the leading infectious cause of death in the Unites States 4 . SARS-CoV-2-targeting mRNA vaccines have become available for individuals six months of age and older 5,6,7,8,9,10,11 .…”
Section: Introductionmentioning
confidence: 99%
“…COVID-19 is the eighth leading cause of death in minors in the US and has negatively affected pediatric populations worldwide . Vaccination of children can mitigate risk of complications from SARS-CoV-2 infections and support their uninterrupted access to education and healthy psychosocial development .…”
Section: Introductionmentioning
confidence: 99%